PSYCHOSOCIAL WORK ENVIRONMENT AND SICKNESS ABSENCE: THE ROLE OF GENDER - Acquaah, Frank Amishadai Amoah; Sarfo, Jacob Owusu (European Scientific Journal, ESJ, 2014)
The aim of this study was to investigate the effect gender has on the relationship between work-related psychosocial environment and work absence due to sickness. Using the stress profile questionnaire, results show that work control and influence was the major contributor of sickness absence among men. However, burden of workload and levels of work control and influence influenced sickness absence among women. When both men and women were compared on the scale of sickness absence, a significant relationship existed between gender on workload and level of control rather than resources.The study has research, health and managerial implications.